Analysis of gauge glass failure possibility for boiler - Nur Farida, Ismail (2007)
The heating process in the boiler is an operation that carried in 24 hours a day. The boiler operates under high temperature and pressure. There is always a possibility for the fitting of the boiler to have failure. The purpose of this study is to find the failure possibility of the gauge glass through literature and simulation. The gauge glass will fail due to stress, temperature and fittings problem. This analysis is concentrate on the glass as the glass is brittle and have higher tendency to fail rather than other fittings and connector. As the failure due to stress and temperature is unavoidable, the inspection must be done periodically. During the inspection, overall boiler must be checked to make sure there is no faultiness to the part that attached to the boiler especially gauge glass. If the is a problem occur during inspection, this gauge glass have to be repair or replace.